2018
DOI: 10.1111/ina.12502
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a portable air cleaner in removing aerosol particles in homes close to highways

Abstract: Outdoor traffic-related airborne particles can infiltrate a building and adversely affect the indoor air quality. Limited information is available on the effectiveness of high efficiency particulate air (HEPA) filtration of traffic-related particles. Here, we investigated the effectiveness of portable HEPA air cleaners in reducing indoor concentrations of traffic-related and other aerosols, including black carbon (BC), PM , ultraviolet absorbing particulate matter (UVPM) (a marker of tobacco smoke), and fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 69 publications
(144 reference statements)
2
57
1
Order By: Relevance
“…In all of the study homes 39 and FVC and increases in biomarkers of neutrophilic inflammation in adults with mild-to-moderate asthma; however, it should be noted that the participants in the aforementioned study did not note any symptomatic changes. 62 To understand if the particle concentrations were high or low, we compared to other studies.…”
Section: Discussionmentioning
confidence: 81%
“…In all of the study homes 39 and FVC and increases in biomarkers of neutrophilic inflammation in adults with mild-to-moderate asthma; however, it should be noted that the participants in the aforementioned study did not note any symptomatic changes. 62 To understand if the particle concentrations were high or low, we compared to other studies.…”
Section: Discussionmentioning
confidence: 81%
“…Avoiding close proximity to major roads is recommended as it is well known that the air pollution level is closely correlated with the distance from a given road. Moreover, if possible, the use of air cleaners at home can be helpful in decreasing the air pollution level inside the house . The wearing of masks is generally advised, but evidence is currently limited .…”
Section: Air Pollutionmentioning
confidence: 99%
“…Moreover, if possible, the use of air cleaners at home can be helpful in decreasing the air pollution level inside the house. 21,22 The wearing of masks is generally advised, but evidence is currently limited. 23,24 There is a marked variance between countries in the type of mask used, and masks should be assessed to ensure they can filter 2.5 μm particulate matter.…”
Section: Air Pollutionmentioning
confidence: 99%
“…Such information would be valuable for developing guidelines for the use of these cleaners in residences. Several related studies have been conducted in residential buildings [15][16][17][18][19][20]. These studies found that portable air cleaners used in residences could reduce concentrations of particles from outdoor and indoor sources by 32%-68%.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies on the efficiency of air cleaners have been conducted for particles from indoor sources such as smoking and wood burning in winter. Some studies have focused on dust events [21] or on residences located close to highways [20]. To the best of our knowledge, no study has evaluated the efficiency of a portable air cleaner in real-world residences in urban cities of south China, where household natural ventilation rates are often large and outdoor air quality is often bad.…”
Section: Introductionmentioning
confidence: 99%